(Im)politeness in Ancient Egypt : Norms, Wit, and Rudeness in Texts from Pharaonic Times through Late Antiquity - Almansa-Villatoro, Maria Victoria; Motte, Aurore (Language and Linguistics E-Books Online, Collection 2025., 2026)
(Im)politeness in Ancient Egypt is the first book-length study of (im)politeness in ancient Egyptian texts. Leading experts in their respective corpora examine a range of textual sources spanning approximately 2,000 years, using the latest frameworks for analyzing language in usage. This edited volume asks how ancient Egyptians adapted and modified their language to persuade, complain, or mock, and how they assessed the risks and benefits of communicating with those above or below them in the social hierarchy. The papers explore whether ancient Egyptians used politeness freely and strategically, or were constrained by mandatory social rules. The documents presented, translated, and analyzed in this book include personal letters, ritual utterances, fictional stories, dialogue captions in tomb scenes, and messages to dead relatives.